URGENSI SHALAT DALAM MEMBENTUK KARAKTER MUSLIM MENURUT QURAISH SHIHAB - Anggi Wahyu Ari (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Nowadays, majority of Muslims have less awareness about meaning and real substance of prayer. According to Quraish Shihab, a Muslim who has understood about meaning and educational values in prayer, actually his attitude, character, and the way of thinking should be based on Al- Qur’an and Hadith as well. This paper tries to assess how important the sense and meaning of prayer for a servant to Allah SWT. Prayer is said as a greatest thing because prayer involves three components of human as well; first is body movement, second is oral speech, and third is instinct in the heart that are intended to Allah SWT. All of these components can create good character to Muslim in interaction of Allah and interaction of others